FINANCIAL LITERATION FOR NEW BUSINESSES FOR PROSPECTIVE Internships IN JAPAN - Novfitri Landong Namora Sihombing; Aji Erlangga; Amrizal (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2020)
Financial literacy as one of the basic literacy offers a set of knowledge and skills to manage financial resources effectively for the welfare of life as well as basic needs for everyone to minimize, find solutions, and make the right decisions in financial problems. Financial literacy also provides knowledge about the management and utilization of resources as ammunition for the formation and strengthening of Indonesian human resources who are competent, competitive, and have integrity in facing competition in the era of globalization and free markets and also as citizens and citizens of the world who areresponsible. responsible for the preservation of nature and the environment in meeting the needs of life and welfare.If financial literacy is related to business financial management, it is how to increase the ability of aspiring new entrepreneurs to make financial planning and processing for their new business. In business financial management, it is divided into 3 parts: 1) activities of using funds, 2) activities of obtaining funds, 3) activities of using funds.ITB-AD conducts training programs for prospective interns in Japan by providing knowledge and skills in financial management. This knowledge is given to them before leaving their internship in Japan and after returning from Japan, so that they understand financial and business management in a simple way.